Ruby on rails : up and running - Tate, Bruce, 1965- (O'Reilly, 2006)
Ruby on Rails is the super-productive new way to develop full-featuredweb applications. With Ruby on Rails, powerful web applications thatonce took weeks or months to develop can now be produced in a matter ofdays. If it sounds too good to be true, it isn't. If you're like a lot of web developers, you've probably consideredkicking the tires on Rails - the framework of choice for the newgeneration of Web 2.0 developers. Ruby on Rails: Up and Running takes you out for a test drive and shows you just how fastRuby on Rails can go. This compact guide teaches you the basics of installing and using bot.